2009
DOI: 10.1380/ejssnt.2009.93
|View full text |Cite
|
Sign up to set email alerts
|

Ionization Mechanism in Surface Plasmon Enhanced Laser Desorption/Ionization

Abstract: We researched contribution of a charge transfer (CT) effect to desorption/ionization mechanism in our ultra-high sensitive laser desorption/ionization mass spectrometry based on surface plasmon (SP) excitation (SPLDI-MS). A quantity of CT electrons between a metal surface and sample molecules estimated from Raman measurement is correlated to a mass signal intensity of sample molecule in our SPLDI-MS method. A sample system with a larger quantity of CT electrons gave a higher mass signal intensity. Efficient us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…26,27 Additionally, the ionization and desorption of analytes were also reported to occur through nonthermal processes by surface plasmon excitation to generate large density of charges as well as by the laser ablation to generate laser-induced plasma. 28,29 Among the various nanomaterials, TiO 2 -based nanostructures of nanoparticles, nanowires, and nanofilms have been used as solid matrices for LDI MS. This is because TiO 2 is an n-type semiconductor with a photocatalytic activity under UV light and can efficiently generate electron−hole pairs for ionization of analytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Additionally, the ionization and desorption of analytes were also reported to occur through nonthermal processes by surface plasmon excitation to generate large density of charges as well as by the laser ablation to generate laser-induced plasma. 28,29 Among the various nanomaterials, TiO 2 -based nanostructures of nanoparticles, nanowires, and nanofilms have been used as solid matrices for LDI MS. This is because TiO 2 is an n-type semiconductor with a photocatalytic activity under UV light and can efficiently generate electron−hole pairs for ionization of analytes.…”
Section: Introductionmentioning
confidence: 99%
“…After the UV laser irradiation, reductive electrons at conduction bands and holes at valence bands are produced, and analytes are ionized through reduction with exited electrons and oxidation with remaining holes . (3) In the case of noble metal nanomaterials, free electrons absorb UV laser energy and ionize the analytes through thermal energy transfer. , Additionally, the ionization and desorption of analytes were also reported to occur through nonthermal processes by surface plasmon excitation to generate large density of charges as well as by the laser ablation to generate laser-induced plasma. , …”
Section: Introductionmentioning
confidence: 99%
“…Besides the importance of NP size [ 59 , 72 ] and composition [ 60 ], discussed in the previous section, other factors have been reported to influence the LDI process. Since the early appearance of nanostructures for MS applications, it was shown that surface plasmon (SP) excitation could enhance both the electromagnetic field and the charge transfer between the NP and the adsorbate molecules [ 73 ], thus affecting both desorption and ionization phenomena [ 59 , 74 , 75 ]. Such correlation was deeply studied for gold nanostructures, demonstrating that a visible laser at 532 nm, which can be resonantly absorbed by AuNPs (SP band falling in the 500 nm–600 nm range), positively affects analyte detection [ 74 , 75 , 76 , 77 ], provided that no aggregation phenomena occur.…”
Section: Other Aspects Influencing Desorption/ionization Mechanismmentioning
confidence: 99%